The strategy of local communities in promoting and enhancing local investment in light of Investment Law 22-18 - Nouioua, Houda (Journal of Human Sciences, 2025)
Economic approaches differ from political and social approaches, and although it is difficult and impossible to separate them, one of the most prominent aspects of state formation is the economic aspect, which remains crucial for the advancement of other sectors. The success of investment in any country is considered one of the indicators of economic takeoff. Algeria is among the countries that have engaged in numerous partnerships to attract various investments, especially foreign ones. However, several factors have hindered this, including that all investments were concentrated in the energy sector, primarily relying on oil, leading to what is termed a rentier economy. Additionally, a strategic mistake by the state has been the marginalization of local communities in wealth creation, assigning them a non-productive administrative role. Given all these issues, particularly those faced by local communities, it has become imperative for the government to focus on local development and investment to achieve the main goal of reducing regional disparities between poor and wealthy municipalities and provinces. Investment is considered one of the 16 commitments among the 54 commitments the state seeks to fulfill, aligning with the new directions of the Algerian government, aiming to make local communities an effective economic agent to promote local investment and ultimately achieve comprehensive local development.